PERAN ETIKA AUDITOR, PENGALAMAN AUDITOR, KOMPETENSI AUDITOR DAN PERILAKU AUDIT DISFUNGSIONAL TERHADAP KUALITAS AUDIT - Efa Suryaningsih; Nibras Anny Khabibah (JOEL: Journal of Educational and Language Research, 2022)
In auditing audit ethics, auditors' work experience, auditor competence, and functional audit behavior have an important role in determining audit quality. This research is included in qualitative research. The author uses the method of literature review and descriptive research techniques. The purpose of this study is to determine and analyze the role of auditor ethics, auditor experience, auditor competence and functional audit behavior on audit quality. The results of this study indicate that auditor ethics Auditor experience, auditor competence and dysfunctional behavior also have a positive effect on audit quality.